Nonpolar Resistive Switching in Ag@TiO2 Core-Shell Nanowires - BOLAND, JOHN (My University, 2017)
Nonpolar resistive switching (RS), a combination of bipolar and unipolar RS, is demonstrated for the first time in a single nanowire (NW) system. Exploiting Ag@TiO2 core–shell (CS) NWs synthesized by postgrowth shell formation, the switching mode is controlled by adjusting the current compliance effectively, tailoring the electrical polarity response. We demonstrate ON/OFF ratios of 105 and 107 for bipolar and unipolar modes, respectively. In the bipolar regime, retention times could be controlled up to 103 s, and in the unipolar mode, >106 s was recorded. We show how the unique dual-mode switching behavior is enabled by the defect-rich polycrystalline material structure of the TiO2 shell and the interaction between the Ag core and the Ag electrodes. These results provide a foundation for engineering nonpolar RS behaviors for memory storage and neuromorphic applications in CSNW structures.
PUBLISHED
Keywords: Nano-wire